Teachers' technological competencies in enhancing teaching and learning in secondary schools in Tanzania - Tumaini Kalinga; Placidius Ndibalema (Academy of Cognitive and Natural Sciences, 2023)
The purpose of this study was to investigate level of teachers' technological competencies and the effect of teachers' age, gender, educational level and teaching experience in relation to their technological competencies they hold. Questionnaires were used to collect the data from 139 teachers from selected schools using simple random and purposive sampling procedures. Descriptive and inferential statistics were carried out using SPSS software version 23. The study found that majority of teachers were at the first level of technological competency (KA). It was also found that there was significant difference between teachers' level of education and technological competencies they hold. However, the study found that there is no significant difference between teachers' gender, age and working experience and technological competencies they hold at p-value of 0.05, though there were some variations. The study recommends that provision of training among teachers should focus on uplifting teachers from KA level to another levels.